(untitled) (Revista de História da UEG (REVHIST), 2022)
Researches that approach the pombaline period appear in a low volume within education historiography in Brazil; in addition, they are marked by diverse representations, which are often dichotomic. In this sense, there is a need to renew pombaline studies. This research seeks to contribute to such purpose, given that it aims to gather sources used in books and journal publications authored by Brazilians. 245 texts were found. Their references were analyzed and classified, based on the groups Alves (2005) proposes, in classical works, documental sources, and historiography. The latter was subdivided in theses and dissertations, publications in journals and books, dictionaries, and biographies. Historiography, especially books, concentrates more recurrences within the works analyzed. Moreover, few authors study documental sources. Keywords: Colony. Historical sources. Brazilian historiography.